(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article analyzes the study and cultivation of Manchurian apricot (Armeniaca Mandshurica (Maxim.) Kostina) and pinnate hawthorn (Crataegus pinnatifida Bge). Information has been collected on the biological characteristics of these species in their natural habitat, and the results of studying the biology of specimens growing in the conditions of the Tashkent Botanical Garden are presented. These species are promising for introduction into the forestry of the Republic of Uzbekistan, due to their drought resistance.